A case of primary pulmonary atypical carcinoid with EML4-ALK rearrangement. Issue 1 (2nd January 2020) - Liu, Na; Wang, Jingjing; Fu, Xiao; Zheng, Xiaoqiang; Gao, Huan; Tian, Tao; Ruan, Zhiping; Yao, Yu
ABSTRACT: Targeted therapy has revolutionized the treatment pattern of advanced drive gene mutation positive non-small cell lung cancer (NSCLC). Advanced testing techniques enable physicians to detect these gene alterations in the clinic, thereby offering targeted therapies as treatment options to their patients. In this article, we reported a 52-year-old Chinese female with a pulmonary nodule in her left lower lung. After thoracoscopic lobectomy, a histopathological diagnosis of moderately differentiated atypical carcinoid (AC) was made. Anaplastic lymphoma kinase (ALK) rearrangement was detected, which is a rare phenomenon in AC. After the failure of chemotherapy and radiotherapy, the patient started taking crizotinib, subsequently with ceritinib, and then alectinib. This sequential therapy approach has significant clinical benefits for the patient. This article reviewed the clinical significance and drug resistance mechanism of ALK rearrangement in lung cancer. We also discussed recent and ongoing researches and applications of ALK-tyrosine kinase inhibitors (ALK-TKIs).